1994
DOI: 10.1210/jcem.79.1.8027230
|View full text |Cite
|
Sign up to set email alerts
|

Insulin response to intravenous glucose in patients with anorexia nervosa showing low insulin response to oral glucose.

Abstract: To investigate the cause of a low insulin secretory response to an oral glucose tolerance test (OGTT) in patients with anorexia nervosa (AN), we performed iv glucose tolerance tests (IVGTT) before and after treatment in 36 anorectic patients who showed low insulin secretion in response to the OGTT. These patients were subdivided into 3 groups by glucose tolerance curves during the OGTT: normal type, blood glucose level peaking 60 min or earlier after oral glucose ingestion; delayed type, blood glucose level pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The AUC was calculated using the trapezoidal approach. The K G was calculated as the slope of the decimal log of the glucose concentration at 10 -30 min after glucose injection (20,21).…”
Section: Intraperitoneal Glucose Tolerance Testsmentioning
confidence: 99%
“…The AUC was calculated using the trapezoidal approach. The K G was calculated as the slope of the decimal log of the glucose concentration at 10 -30 min after glucose injection (20,21).…”
Section: Intraperitoneal Glucose Tolerance Testsmentioning
confidence: 99%
“…Such data support the hypothesis that elevated ghrelin secretion reflects energy demand and stimulates GH secretion in AN. However, antibodies for measuring plasma ghrelin levels in previous studies have been against C-terminus ghrelin (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) (3,5,6), ghrelin (1-11) (7) or full-length ghrelin with or without octanoylation at Ser 3 (8 -11). Concentrations of intact ghrelin actually represent less than 10% of total circulating ghrelin levels, which include acylated and desacylated ghrelin immunoreactivities (12).…”
mentioning
confidence: 99%
“…Metabolic changes in patients with AN, particularly carbohydrate metabolism, have been well documented (Herzog & Copeland, 1981). Some studies have revealed changes in insulin sensitivity (Kiriike et al, 1990), insulin resistance (Scheen, Castillo, & Lefebvre, 1988), and a spectrum of glucose and insulin response patterns to the oral glucose tolerance test (OGTT; Nozaki et al, 1994). Several studies also suggest that carbohydrate metabolism is closely related to nutritional status and eating behavior (Russell, Hooper, & Hunt, 1996).…”
Section: Introductionmentioning
confidence: 99%